Division Of Joint Property In The Panyabungan City Community, Mandailing Natal Regency, As Reviewed From UU No. 1 Of 1974 And KHI - David Nwanna Dumbiri; Zuhdi Hasibuan (Program Pascasarjana UIN Sumatera Utara Medan, 2017)
The purpose of this thesis is to understand the concept of Law No. 1 of 1974 and the KHI regarding the division of joint property, to understand the distribution of joint property in Panyabungan City District, and to identify the factors underlying the division of joint property in Panyabungan City District. The research method used by the author is field research, where all data is obtained from the field. In this approach, the research is conducted in a natural setting but is preceded by some form of intervention from the researcher. The research will be conducted in Panyabungan City District, Mandailing Natal Regency. This article presents findings that the general understanding of the distribution of joint property among the people of Panyabungan Kota sub-district is still lacking. Only community leaders, and even then, only partially understand the concept. Many people in Panyabungan Kota sub-district still do not share joint property. However, some people do share joint property. However, the existing system of sharing joint property in this sub-district is still far from what is stipulated in community regulations. The dominant distribution of joint property is based on whoever has the most or who always earns the living in the household, who receives the largest share. The factors contributing to the poor implementation of joint property distribution in Panyabungan Kota sub-district are a general lack of understanding of joint property distribution, factors of justice, and economic factors.